2015
DOI: 10.1177/2049936115622891
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the understanding of antibiotic resistance in Clostridium difficile infection

Abstract: Clostridium difficile epidemiology has changed in recent years, with the emergence of highly virulent types associated with severe infections, high rates of recurrences and mortality. Antibiotic resistance plays an important role in driving these epidemiological changes and the emergence of new types. While clindamycin resistance was driving historical endemic types, new types are associated with resistance to fluoroquinolones. Furthermore, resistance to multiple antibiotics is a common feature of the newly em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
275
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(318 citation statements)
references
References 166 publications
(273 reference statements)
10
275
0
13
Order By: Relevance
“…60 This increase was associated with the emergence of hypervirulent C. difficile strains. 61 The most prominent hypervirulent strain is PCR-ribotype (RT) 027 which is responsible serious and frequently recurring infections and many of these strains carry an MDR phenotype. A European survey in 2005 indicated that 55% of 148 isolates with resistance to at least one antibiotic was multidrug resistant.…”
Section: Gram-positive Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…60 This increase was associated with the emergence of hypervirulent C. difficile strains. 61 The most prominent hypervirulent strain is PCR-ribotype (RT) 027 which is responsible serious and frequently recurring infections and many of these strains carry an MDR phenotype. A European survey in 2005 indicated that 55% of 148 isolates with resistance to at least one antibiotic was multidrug resistant.…”
Section: Gram-positive Bacteriamentioning
confidence: 99%
“…Among these RT078 cause Clostridium difficile disease both in community and hospital settings, and also in animals. 61 …”
Section: Gram-positive Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…C. difficile also generally displays resistance to second-generation cephalosporins but shows less resistance to third-generation cephalosporins. However, resistance to moxifloxacin and gatifloxacin has been detected in 34% of strains analysed [29]. Tenover and colleagues analysed the resistances of different ribotypes to clindamycin, metronidazole, moxifloxacin and rifampin.…”
Section: Resistancementioning
confidence: 99%
“…Clostridium difficile has a number of putative β-lactamase genes that are probably involved in resistance to β-lactam antibiotics [29]. A ribosomal methylation mechanism related to macrolide resistance in C. difficile has been described (Ref).…”
Section: Resistancementioning
confidence: 99%